TOWARDS NEUROCOSMOPOLITANISM: AN ECOSOMATIC READING OF CONTEMPORARY OWN-VOICES AUTISTIC WRITINGS - Noor Nedal Said Alzaghal (جامعة النجاح الوطنية, 2025)
This thesis, drawing on literary neurodiversity studies, explores the oppressive hierarchal system of power, neuronormativity, through the lens of Autistic authors and from the perspective of Autistic characters in Elle McNicoll’s A Kind of Spark (2021) and Anna Whateley’s Peta Lyre’s Rating Normal (2021). These novels highlight Autistic voices and their counter narratives towards a neurocosmopolitan society. This thesis follows the medical humanities approach, which studies the intersection between the humanities disciplines and questions regarding health and well-being of individuals. I have examined the displayed neuronormativity and its detrimental impact on Autistics’ general wellbeing in both literary texts, and illustrated the literary texts’ drive towards neurocosmopolitanism through analyzing the ecocritical aspects of the narrative and showcasing how both Addie and Peta find peace in nature, and fantasize about it as an escape from neuronormative society. I also highlight the role of nature in reclaiming Autistic identity. Through this deep dive into Autism in own-voices literature, we can sense the importance of exploring and analyzing literary texts that express the voices of the marginalized in order to lessen the neurotypical ignorance of other neurodivergent individuals around us and eradicate the persisting stigma surrounding Autism and other neurodivergent individuals.
نحو النيروكوزموبوليتانية: قراءة ايكوسوماتية لكتابات كتاب متوحدين